The financial crisis in the United States, 1893-4 - Battersby, T. S. F. (Statistical and Social Inquiry Society of Ireland, 1894)
The year 1893 in America stands unique in that it presents an unrivalled record of failures of solvent banks, corporations, firms, and individuals in a country having unsurpassed facilities for production and distribution. In six short months all this was changed to depression, fear, weakness in trade, and complete collapse in credit. A few weeks later almost all banks refused to pay even the cheques of their own customers with balances to their credit. Simultaneously, a panic set in on the Stock Exchange, resulting in an unparalleled fall in prices of all securities. Brokers praotically ceased operations, and Wall Street and the Corn Exchange, Chicago, were idle; business generally came to a standstill. The gold reserve in the national treasury reached a substantial deficit and labour troubles rapidly developed to a dangerous magnitude. Such is a brief outline of the commercial and financial conditions in the United States in the month of September, 1893, and I propose now to consider the causes which led to this cyclone.
Read Tuesday, 26th June, 1894
Keywords: American finance; Financial crises; 314.15